IMPLEMENTASI TAX HOLIDAY DALAM RANGKA MENINGKATKAN FOREIGN DIRECT INVESTMENT DI INDONESIA - Noviandari Sari Utami (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study was conducted to analyze Tax Holiday in Indonesia in order to increase FDI based on Minister of Finance Regulation Number 130 year of 2011. This study is a qualitative research. The author conducted in-depth interviews with 3 interviewees from taxation academics, the representative of Astra Group and staff of Sub Supervision Enterprises Mineral Exploration Ministry of Energy and Mineral Resources. Moreover, the author also collected data from written document in form of regulation, other research, books and internet. The result shows that Tax Holiday before Minister of Finance Regulation Number 130, had not been able to increase FDI due to political and economic instability. Tax Holiday on Minister of Finance Regulation Number 130 is able to increase FDI inflow in Indonesia because of the certainty of the criteria of the recipient, the clarity of procedures and the involvement of several state agencies.